2017
DOI: 10.1021/acs.orglett.7b00041
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Synthesis of o-Benzenediboronic Acids via Ir-Catalyzed o-C–H Borylation Directed by a Pyrazolylaniline-Modified Boronyl Group

Abstract: Ir-catalyzed ortho-directed C-H borylation of pyrazolylaniline (PZA)-modified arylboronic acids with bis(pinacolate)diboron afforded o-benzenediboronic acids in which two boronyl groups are differentially modified by pinacol (PIN) and PZA. By using this borylation after nondirected Ir-catalyzed C-H borylation, o-benzenediboronic acids are conveniently synthesized from unfunctionalized arenes. The differentially modified o-benzenediboronic acids undergo selective oxidation and Suzuki-Miyaura cross-coupling at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Surprisingly, the use of Plenio’s conditions afforded 28 as the main product, resulting from the directing group functionalization (entries 3 and 4). Such a regioselectivity switch between catalytic rhodium-catalyzed silylation and iridium-catalyzed borylation is known and was also recently documented in the benzene series using the same boron anthranilamide directing group . However, even if it is known that borylation is sensitive to ortho substituents, the exact origin of this reversal is not totally understood .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, the use of Plenio’s conditions afforded 28 as the main product, resulting from the directing group functionalization (entries 3 and 4). Such a regioselectivity switch between catalytic rhodium-catalyzed silylation and iridium-catalyzed borylation is known and was also recently documented in the benzene series using the same boron anthranilamide directing group . However, even if it is known that borylation is sensitive to ortho substituents, the exact origin of this reversal is not totally understood .…”
Section: Resultsmentioning
confidence: 99%
“…Such a regioselectivity switch between catalytic rhodium-catalyzed silylation and iridium-catalyzed borylation is known 53 and was also recently documented in the benzene series using the same boron anthranilamide directing group. 54 However, even if it is known that borylation is sensitive to ortho substituents, the exact origin of this reversal is not totally understood. 53 Taking into account the generally accepted mechanism of iridium-catalyzed borylation, 55 this might indicate that the directing group would not be effective to coordinate the iridium catalyst surrounded by three pinacol residues and the bipyridine ligand.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Site-selective π-extension of unactivated polyarenes can also be achieved in a sequential manner using C–H metalation chemistry, followed by a more conventional cross-coupling step. This strategy has been used in recent years to access materials-oriented molecules using either site-selective borylation or silylation techniques, then Suzuki–Miyaura or Hiyama–Denmark cross-couplings, respectively. It has also been shown that this process can proceed in a one-pot fashion …”
Section: Sequential π-Extension By C–h Metalationmentioning
confidence: 99%
“…A plethora of strategies to realize the latter objective has been pursued. The invention of various removable or modifiable [20,21,22], traceless [23], or otherwise transient [24,25,26,27,28,29] directing groups has formed a sizeable category in and of itself within the field of C-H functionalization catalysis.…”
Section: Introductionmentioning
confidence: 99%